Antibodies against polysaccharide type 3 and pneumococcal proteins demonstrate synergistic protective effect in a highly virulent type 3 invasive disease model in mice - Stevenson, Taylor C.; Burke, Heidi; Roggensack, Sara E.; Pratt, Anthony; Hossain, Aquib; Ghosh, Pallab; Besin, Gilles; Lu, Yingjie; Zhang, Fan; Malley, Richard; Sebastian, Shite (Frontiers in Immunology, 2025)
Streptococcus pneumoniae serotype-3 (ST-3) continues to be a major contributor to pneumococcal disease burden despite its inclusion in multivalent pneumococcal conjugate vaccines (PCV). Therefore, there is a pressing need to develop vaccines that can elicit more versatile immune responses against ST-3. To this purpose, our approach was to evaluate MAPS technology-based vaccine candidates in which biotinylated pneumococcal polysaccharides are non-covalently complexed with biotin-binding proteins. One such protein was SPP2, a fusion protein containing a nonhemolytic mutant of pneumolysin (Ply). The immunogenicity of SPP2 as a component of a vaccine candidate containing over 30 pneumococcal capsular polysaccharides, including ST-3 capsule (CPS3), was evaluated in rabbits. The vaccine demonstrated strong immunogenic properties, producing high titers of Ply-neutralizing antibodies and a robust opsonophagocytic antibody response to ST-3. A highly lethal ST-3 pneumococcal invasive disease model, in which antibodies to CPS3 alone are not highly protective, was developed to evaluate whether the inclusion of SPP2 can provide synergistic protection. Active immunization of mice with SPP2- and CPS3-containing vaccine and passive immunization of mice with antisera containing anti-CPS3 and anti-SPP2 antibodies conferred significant protection against death, whereas immunization against either antigen alone did not confer protection, suggesting a synergistic interaction between the protein- and polysaccharide-directed antibodies. These findings strongly support a vaccine approach that includes both pneumococcal polysaccharides and highly conserved disease-specific proteins to overcome the clinical resistance of ST-3 pneumococcal disease to traditional PCVs.